Self-healing and self-recovering systems under the spatial grasp model - Sapaty, Peter (Emerald Publishing Limited, 2025)
In an era where the resilience of large-scale systems is paramount, Self-Healing and Self-Recovering Systems under the Spatial Grasp Model explores the transformative potential of self-recovery--often termed 'self-healing' or 'remediation'. This essential feature is crucial for critical infrastructures that underpin global prosperity, security, and sustainability. Author Peter Simon Sapaty begins by establishing foundational definitions of self-healing systems and reviewing existing literature on self-healing infrastructures and networks, along with an analysis of prevailing network threats. He introduces the innovative Spatial Grasp Model and its accompanying Spatial Grasp Language (SGL), detailing how these frameworks enable distributed networks of any scale and topology to operate in a self-analysing, self-healing, and self-repairing manner--effectively rendering them 'immortal'. The compact and clear holistic spatial solutions provided by SGL stand in contrast to traditional models reliant on interacting agents. The implications of this research extend to global networks, offering practical solutions for a range of applications, including transport systems recovery post-pandemics, debris clearance from Earth's orbit, and the enhancement of security infrastructures. This work is essential for researchers, practitioners, and policymakers interested in advancing the design and implementation of resilient infrastructures in an increasingly interconnected world.
Includes index.
Keywords: Self-care, Health.; Business & Economics -- Occupational Health & Safety.; Business ethics and social responsibility.; Health and safety in the workplace.; elektronické knihy; electronic books